Pengaruh Nilai Publik Terhadap Keterlibatan Kerja Dengan Efikasi Diri Sebagai Variabel Mediasi - Muhammad Nur; Adi Rahmat; Fahmi Oemar; Didik Siswanto (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2025)
This study aims to analyze the effect of public value on work engagement with self-efficacy as a mediating variable. Universitas Lancang Kuning was selected as the research object to explore how the public value created by an educational institution can enhance employee work engagement through the mechanism of self-efficacy. This research employs a quantitative method with a survey approach. Data were collected using a Likert scale (1-5) questionnaire distributed to lecturers and administrative staff at Universitas Lancang Kuning. The data analysis technique used was Structural Equation Modeling (SEM) with the assistance of Warp PLS 8.0 software to examine the relationships between variables, including the mediating effect of self-efficacy. The results show that public value has a positive and significant effect on work engagement. Additionally, public value positively influences self-efficacy, which, in turn, enhances employee work engagement. Self-efficacy acts as a mediating variable in the relationship between public value and work engagement, meaning that part of the effect of public value on work engagement can be explained through the increase in employees' self-efficacy. This study reinforces the theory that public value can enhance work engagement through increased self-efficacy. In the context of higher education, universities can boost employee work engagement by emphasizing their social role and institutional impact on society. These findings have implications for human resource management in designing strategies that focus on strengthening public value and developing employees' self-efficacy to enhance their commitment to their work